Accelerated test device and method for anti-fouling performance of hydrogen production diaphragm for alkaline electrolytic water

By designing an accelerated testing device and method for the antifouling performance of alkaline water electrolysis hydrogen production membranes, the deposition process of catalyst particles on the membrane is simulated, the surface resistance change is monitored in real time, and an antifouling index is introduced. This solves the shortcomings of existing testing methods and realizes dynamic evaluation and failure prediction of the membrane under complex operating conditions.

CN122631720APending Publication Date: 2026-08-25SUNGROW HYDROGEN SCI &TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610739779.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing testing methods cannot effectively simulate the deposition behavior of catalyst particles on the membrane during alkaline water electrolysis hydrogen production, and the evaluation indicators are limited, making it difficult to reflect the long-term stability and failure mechanism of the membrane under complex operating conditions.

Method used

An accelerated testing device for the antifouling performance of an alkaline water electrolysis hydrogen production membrane was designed, comprising an electrolyzer module, an electrolyte circulation module, a particle quantitative addition module, and an online monitoring module. By simulating the catalyst deposition process under real-world electrolyzer conditions, the device monitors the change in sheet resistance of the membrane in real time and introduces an antifouling index as an evaluation indicator.

Benefits of technology

It enables quantitative evaluation of the anti-fouling performance of diaphragms under dynamic operating conditions, and can predict their long-term stability and failure time, guiding operation and maintenance and selection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122631720A_ABST
    Figure CN122631720A_ABST
Patent Text Reader

Abstract

The application relates to an anti-pollution performance accelerated testing device and method of a hydrogen production diaphragm of alkaline electrolytic water, and belongs to the field of electrochemistry. The method simulates the process of catalyst deposition under the real working condition of an electrolytic tank by adopting dynamic addition of catalyst particles, is closer to the actual operation environment of the electrolytic tank, introduces an anti-pollution index as an evaluation index based on test data, realizes quantitative evaluation of the anti-pollution performance of the diaphragm, can reflect the stability of long-term operation, and can also be used for estimating the failure time of the diaphragm and can be used for guiding operation and maintenance and selection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an accelerated testing device and method for the antifouling performance of alkaline water electrolysis hydrogen production membranes, belonging to the field of electrochemistry. Background Technology

[0002] Alkaline water electrolysis (AWE) is one of the most mature and relatively low-cost hydrogen production processes currently in industrial use. Its core principle is based on an electrochemical reaction, typically using potassium hydroxide (KOH) solution as the electrolyte, and utilizing an electric field to decompose water molecules. Its key technological advantages lie in the use of mature nickel-based metal catalysts and alkali-resistant materials; however, its performance bottleneck mainly lies in the matching of the electrodes and the diaphragm.

[0003] In current alkaline water electrolysis hydrogen production technology, the diaphragm is a key material, and its performance directly affects the energy consumption, safety, and gas purity of the electrolyzer. Current industry standards (such as T / CI 1078-2025 "Test Methods for Composite Diaphragms in Alkaline Water Electrolysis") mainly specify the initial performance tests of the diaphragm, including static tests such as sheet resistance, bubble point pressure, porosity, and alkali resistance loss. However, these tests do not fully cover the long-term dynamic performance and failure mechanisms of the diaphragm under the complex operating conditions of actual water electrolysis hydrogen production. In addition, during long-term operation of the electrolyzer, catalyst particles on the electrode surface may detach due to bubble erosion, thermal stress, or chemical corrosion. The detached catalyst particles (such as Raney nickel powder and nickel oxide) will deposit on the surface and inside the diaphragm, leading to increased sheet resistance and decreased gas purity, which may cause diaphragm failure.

[0004] Existing testing methods have the following shortcomings: 1. Lack of dynamic simulation: Existing test methods are usually carried out under no-current conditions, while in a real electrolyzer, catalyst particles will migrate or deposit under the action of an electric field. Furthermore, existing test methods are difficult to verify the details of how catalyst particles migrate, settle and adhere to the membrane in the solution, making it difficult to simulate the deposition behavior of catalyst particles on the membrane during the operation of the electrolyzer. 2. Limited evaluation criteria: Initial sheet resistance can only reflect the resistance characteristics of the diaphragm under ideal or initial conditions. However, under more complex pollution conditions, pore blockage, membrane damage, and chemical degradation are the main causes of increased resistance. These processes are closely related to time. Therefore, initial sheet resistance cannot reflect the long-term stability of the diaphragm under pollution conditions.

[0005] Therefore, there is an urgent need for a test method that can simulate the actual usage environment and monitor the dynamic changes in the surface resistance of the diaphragm. Summary of the Invention

[0006] The first objective of this invention is to provide an accelerated testing device for the antifouling performance of an alkaline water electrolysis hydrogen production membrane, the device comprising an electrolyzer module, an electrolyte circulation module, a particle quantitative dosing module, and an online monitoring module; The electrolytic cell module is an electrolytic cell used to realize the electrolysis of water and the deposition of particulate matter; the electrolyte circulation module includes a storage tank, circulation pump, flow meter, temperature control unit, electrolytic cell and turbidity meter; the particle quantitative addition module is set in the loop of the electrolyte circulation module, including a simulated catalyst particle quantitative addition device; the online monitoring module includes an electrochemical workstation. Furthermore, the electrolytic cell adopts a zero-gap structure, with nickel braided mesh, nickel stretched mesh or foam nickel electrodes on both sides, and the diaphragm to be tested sandwiched in the middle; Furthermore, the electrolyte circulation module starts from the storage tank, passes through the circulation pump, flow meter, temperature control unit, electrolytic cell and turbidity meter in sequence, and finally returns to the storage tank, forming a complete electrolyte circulation loop; Furthermore, the storage tank serves as both the start and end point of the circuit, and is used to store the electrolyte; Furthermore, a circulation pump is installed at the outlet end of the storage tank to provide circulation power and ensure the continuous flow of electrolyte in the electrolyte circulation module; Furthermore, a flow meter is installed at the outlet of the circulating pump to measure the flow rate of the electrolyte into the electrolyzer module in real time; Furthermore, a temperature control unit is installed between the flow meter and the electrolytic cell to maintain the stability of the electrolytic cell module temperature; Furthermore, the temperature control unit has a temperature control range of 60-90 ℃; Furthermore, a turbidimeter is installed at the other end of the electrolytic cell to monitor the turbidity of the electrolyte in real time and characterize the concentration of suspended particles therein; Furthermore, the electrolyte returns to the storage tank after passing through the turbidimeter, forming an electrolyte circulation loop; Furthermore, a simulated catalyst particle quantitative addition device is set on the electrolyte circulation loop, with one end connected to a turbidity meter and the other end connected to a storage tank, for continuously or pulsedly adding simulated catalyst particles to the storage tank. Furthermore, the electrochemical workstation is connected to the electrodes in the electrolytic cell to measure the surface resistance of the membrane in the electrolytic cell in real time. Furthermore, several pressure sensors are installed on the electrolyte circulation loop to monitor the pressure in the electrolyte circulation loop in real time. Furthermore, the pressure sensor is connected to the pressure tap of the electrolytic cell via a pressure guide tube; The second objective of this invention is to provide an accelerated testing method for the antifouling performance of an alkaline water electrolysis hydrogen production membrane. This method is based on the aforementioned accelerated testing device for antifouling performance. The method simulates the catalyst deposition process under real operating conditions of an electrolyzer and quantifies the antifouling performance of the membrane based on the test data.

[0007] Furthermore, the method includes: Step S1: Pre-treat the membrane to be tested and prepare simulated catalyst particles; Cut the membrane to be tested (composite membrane or PPS membrane) to any desired size between 5×5 cm and 20×20 cm, and soak it in a 30% KOH solution for 24 hours to ensure full wetting; Preparation of simulated catalyst particles: Collect electrode powder detached after actual electrolytic cell operation, or use Raney nickel powder and nickel oxide powder mixed in a mass ratio of 1:5-5:1 as simulated catalyst particles, wherein the particle size distribution of Raney nickel powder and nickel oxide powder is controlled between 0.5-50 μm; Step S2: Calculate the initial sheet resistance of the membrane under test based on the background resistance of the accelerated testing device in the membrane-free state and the sheet resistance of the membrane under test in the condition without simulated catalyst particles; First, the background resistance of the device was measured in the uncoated state. Then, the sheet resistance of the membrane under test was tested without adding simulated catalyst particles. The electrolyte temperature T was recorded, and the initial sheet resistance of the membrane under test was finally obtained. Its value is the surface resistance of the diaphragm under test. With the background resistance of the device The difference is: .

[0008] Step S3: Control the concentration of simulated catalyst particles using an accelerated testing device to achieve accelerated contamination testing of the membrane under test under simulated different operating conditions; Turn on the simulated catalyst particle dosing device and continuously add simulated catalyst particles to the electrolyte, controlling the particle concentration range to be 50-1000 ppm; Operating under corresponding working conditions and monitoring surface resistance online in real time. Changes in electrolyte turbidity (NTU) and particle concentration in the electrolyte; Furthermore, current density The range of variation is 0.1-1.0 A / cm 2 ; Furthermore, when the particle concentration in the electrolyte is below 180 ppm, the simulated catalyst particle quantitative dosing device adds simulated catalyst particles to the storage tank to maintain the particle concentration in the electrolyte at 180-1000 ppm.

[0009] Step S4: Define the antifouling index and calculate the antifouling index of the membrane to be tested based on the data measured in Step S3; Define the pollution resistance index Its expression is: in, The time (in hours) required for the surface resistivity to rise to twice its initial value. This represents the concentration of the added particles; Represents current density.

[0010] Step S5: Based on the antifouling index obtained in Step S4, obtain the quantitative evaluation results of the membrane under test; Anti-pollution index The larger the value, the stronger the antifouling ability of the membrane under test, indicating that the membrane under test has good antifouling performance.

[0011] The beneficial effects of this invention are: This invention provides an accelerated testing device and method for the antifouling performance of diaphragms used in alkaline water electrolysis for hydrogen production. Compared to existing standards, this method differs in its testing conditions and evaluation indicators. It employs dynamic testing conditions containing catalyst particles, more closely mimicking the actual operating environment of an electrolyzer; and it introduces an antifouling index as an evaluation indicator, reflecting long-term operational stability. Furthermore, this method can also be used to estimate the diaphragm's failure time, guiding maintenance and selection. Attached Figure Description

[0012] Figure 1 This is a schematic diagram of the structure of an accelerated testing device for the anti-fouling performance of an alkaline water electrolysis hydrogen production diaphragm provided in Embodiment 1 of the present invention. Detailed Implementation

[0013] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0014] Example 1 This embodiment provides an accelerated testing device for the antifouling performance of an alkaline water electrolysis hydrogen production membrane. The device includes an electrolyzer module, an electrolyte circulation module, a particle quantitative dosing module, and an online monitoring module. The electrolytic cell module is an electrolytic cell used to realize the electrolysis of water and the deposition of particulate matter; the electrolyte circulation module includes a storage tank, circulation pump, flow meter, temperature control unit, electrolytic cell and turbidity meter; the particle quantitative addition module is set in the loop of the electrolyte circulation module, including a simulated catalyst particle quantitative addition device; the online monitoring module includes an electrochemical workstation. The electrolytic cell adopts a zero-gap structure, with nickel braided mesh, nickel stretched mesh or foamed nickel electrodes on both sides, and the diaphragm to be tested sandwiched in the middle. The electrolyte circulation module starts from the storage tank, passes through the circulation pump, flow meter, temperature control unit, electrolytic cell and turbidity meter in sequence, and finally returns to the storage tank, forming a complete electrolyte circulation loop. The storage tank, serving as both the start and end point of the loop, stores the electrolyte. A circulation pump, located at the outlet of the storage tank, provides circulation power, ensuring continuous electrolyte flow in the electrolyte circulation module. A flow meter, located at the outlet of the circulation pump, measures the flow rate of electrolyte into the electrolytic cell module in real time. A temperature control unit, positioned between the flow meter and the electrolytic cell, maintains stable temperature within the electrolytic cell module. The temperature control unit operates within a range of 60-90 °C. A turbidimeter, located at the other end of the electrolytic cell, monitors the turbidity of the electrolyte in real time and characterizes the concentration of suspended particles. After passing through the turbidimeter, the electrolyte returns to the storage tank, forming the electrolyte circulation loop. The simulated catalyst particle quantitative dosing device is set on the electrolyte circulation loop, with one end connected to a turbidity meter and the other end connected to a storage tank, for continuously or pulsedly adding simulated catalyst particles to the storage tank. The electrochemical workstation is connected to the electrodes in the electrolytic cell and is used to measure the surface resistance of the membrane in the electrolytic cell in real time. Several pressure sensors are also installed on the electrolyte circulation loop to monitor the pressure in the electrolyte circulation loop in real time; the pressure sensors are connected to the pressure tap of the electrolytic cell through pressure guide tubes.

[0015] Example 2 This embodiment provides an accelerated testing method for the antifouling performance of an alkaline water electrolysis hydrogen production membrane. This method is based on the accelerated testing device for antifouling performance described in Embodiment 1 above. This method simulates the catalyst deposition process under real operating conditions of an electrolyzer and achieves a quantitative evaluation of the membrane's antifouling performance based on test data.

[0016] This method tests the antifouling performance of the diaphragm by simulating accelerated contamination conditions. The method includes: Step S1: Pre-treat the membrane to be tested and prepare simulated catalyst particles; The ZrO2 / polysulfone composite membrane was cut to obtain a thickness of 0.5 mm and an effective area of ​​100 cm². 2 The membrane to be tested was then soaked in a 30% KOH solution for 24 hours to ensure it was fully wetted. The simulated catalyst particles were obtained by uniformly mixing Raney nickel powder and nickel oxide powder at a mass ratio of 1:1, wherein the particle size of Raney nickel powder and nickel oxide powder was 2.5 μm. Step S2: Test the background resistance of the testing device and the initial surface resistance of the membrane under test; The electrolyte in the electrolytic cell was a 30% (w / w) KOH solution, the temperature was 80℃, and the circulation flow rate was 0.5 m / s. The background resistance of the device was first tested in a membrane-free state. Then, the surface resistivity of the membrane under test was tested without adding simulated catalyst particles. And record the electrolyte temperature T; Background resistance based on the above tests and diaphragm surface resistance The initial surface resistance of the diaphragm under test was calculated. Its value is the surface resistance of the diaphragm under test. With the background resistance of the device The difference is: .

[0017] Step S3: Perform accelerated fouling test on the membrane to be tested in step S2; The particle dosing device was activated to continuously add simulated catalyst particles to the electrolyte to simulate accelerated pollution conditions, controlling the particle concentration at 200 ppm; under constant current density... 0.6 A / cm 2 Under these conditions, accelerated antifouling performance testing was conducted on the diaphragm under test, and the surface resistivity of the diaphragm under test was monitored online in real time. The changes in electrolyte turbidity (NTU) and particle concentration in the electrolyte were monitored. When the particle concentration in the electrolyte was below 180 ppm, a simulated catalyst particle quantitative dosing device was used to add simulated catalyst particles to the storage tank to maintain the particle concentration in the electrolyte at 190-210 ppm.

[0018] The test results are shown in Table 1: Table 1 Test results of the diaphragm under simulated accelerated contamination conditions Step S4: Calculate the antifouling index of the membrane to be tested based on the data measured in step S3; Define the pollution resistance index Its expression is: in, The time (in hours) required for the surface resistivity to rise to twice its initial value. This represents the concentration of the added particles; Represents current density; anti-pollution index The larger the value, the stronger the anti-fouling ability of the membrane under test.

[0019] Substitute the data obtained from the test in step S3 into the expression to obtain the pollution resistance index. It is 5.91; Step S5: Based on the antifouling index, it is concluded that the membrane under test has good antifouling performance.

[0020] Example 3 This embodiment provides a testing method different from that in Embodiment 2. This method uses simulated wind and solar fluctuation conditions to conduct accelerated anti-fouling testing on the diaphragm. The method includes: Step S1: Pre-treat the membrane to be tested and prepare simulated catalyst particles; The PPS woven diaphragm was cut to obtain a thickness of 0.8 mm and an effective area of ​​100 cm². 2 The membrane to be tested was then soaked in a 30% KOH solution for 24 hours to ensure it was fully wetted. The simulated catalyst particles were obtained by uniformly mixing Raney nickel powder and nickel oxide powder at a mass ratio of 1:1, wherein the particle size of Raney nickel powder and nickel oxide powder was 5 μm. Step S2: Test the background resistance of the testing device and the initial surface resistance of the membrane under test; The electrolyte in the electrolytic cell was a 30% (w / w) KOH solution, the temperature was 80℃, and the circulation flow rate was 0.3 m / s. The background resistance of the device was first tested in a membrane-free state. Then, the surface resistivity of the membrane under test was tested without adding simulated catalyst particles. And record the electrolyte temperature T; Background resistance based on the above tests and diaphragm surface resistance The initial surface resistance of the diaphragm under test was calculated. Its value is the surface resistance of the diaphragm under test. With the background resistance of the device The difference is: .

[0021] Step S3: Perform accelerated pollution test on the diaphragm under simulated wind and solar fluctuation conditions after the blank test in step S2. Turn on the particle dosing device and add particles every 6 hours to ensure the particle concentration in the electrolyte instantly rises to 500 ppm, then naturally decreases after 1 hour; current density With 0.2-0.8-0.2 A / cm 2 To simulate wind and solar fluctuations, the current density was switched every 6 hours for cyclical operation. Under these conditions, the anti-fouling performance of the diaphragm under test was accelerated, and the surface resistance of the diaphragm was monitored in real time. The changes in electrolyte turbidity (NTU) and particle concentration in the electrolyte were analyzed; the test results are shown in Table 2. Table 2 Test results of the diaphragm under simulated wind and solar fluctuation conditions Step S4: Calculate the antifouling index of the membrane to be tested based on the data measured in step S3; The expression for the pollution resistance index is: in, The time (in hours) required for the surface resistivity to rise to twice its initial value. This represents the concentration of the added particles; Represents equivalent average current density; anti-pollution index The larger the value, the stronger the anti-fouling ability of the membrane under test; Among them, failure time For 160 hours, the equivalent average current density 0.5 A / cm 2 The final pollution resistance index is obtained. It is 0.64.

[0022] Taking into account the synergistic effects of the simulated catalyst particle concentration acceleration, pulsed dosing acceleration, and temperature and current fluctuations in this embodiment, the actual catalyst particle concentration is approximately 30 ppm. This embodiment uses an instantaneous concentration of 500 ppm, which translates to an acceleration of approximately 17 times. In actual operation, particulate contamination accumulates continuously. This embodiment uses pulsed dosing, and based on experience, the acceleration factor is estimated to be 10 times, ultimately achieving an acceleration of approximately 170-220 times.

[0023] After acceleration, the PPS diaphragm reached twice the surface resistivity in the test in 160 hours. After conversion, the corresponding actual operating conditions are approximately 28,800-35,200 hours (3.3-4 years). According to industrial operation data, under the actual operating conditions of a 1000 Nm³ alkaline electrolyzer, the effective replacement cycle of the PPS diaphragm is 3-4 years (approximately 26,000-35,000 hours). The two are basically consistent, thus indicating that the failure criterion and acceleration factor in the test method provided by this invention are reasonable.

[0024] Example 4 To verify the effectiveness of the testing method provided by the present invention, this embodiment tests different diaphragms. The test is based on an improvement of the device described in Embodiment 1. By setting up a 4-channel parallel electrolytic cell and sharing the same circulation system, synchronous testing of different diaphragms is achieved.

[0025] In this test, the simulated catalyst particles used were a uniform mixture of Raney nickel powder and nickel oxide powder at a mass ratio of 1:1, with a particle size of 3 μm; the remaining test conditions were consistent with those in Example 2; the four types of membranes were: ZIRFON UTP 500 composite membrane, KX500 composite membrane, 1.2 mm thick polyphenylene sulfide (PPS) membrane, and 0.8 mm thick polyphenylene sulfide (PPS) membrane.

[0026] The test results are shown in Table 3: Table 3 Test results of four different diaphragms Under actual working conditions, the sheet resistance of the PPS diaphragm reaches twice the normal value in approximately 3-4 years (0.8 mm thickness) and 4-5 years (1.2 mm thickness); the effective service life of the composite membrane under actual working conditions is 9-12 years. These results are basically consistent with those obtained from the tests in Table 3, indicating that the test method provided by this invention has a certain degree of accuracy and interpretability.

[0027] The principles and implementation methods of the present invention have been described above. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. An accelerated testing method for the antifouling performance of an alkaline water electrolysis membrane for hydrogen production, the method being implemented using an accelerated testing device, simulating the catalyst deposition process under real-world electrolyzer conditions, and combining test data to quantitatively evaluate the membrane's antifouling performance; characterized in that, The method includes: Step S1: Pre-treat the membrane to be tested and prepare simulated catalyst particles; Step S2: Calculate the initial sheet resistance of the membrane under test based on the background resistance of the accelerated testing device in the membrane-free state and the sheet resistance of the membrane under test in the condition without simulated catalyst particles; Step S3: Control the concentration of simulated catalyst particles using an accelerated testing device to achieve accelerated contamination testing of the membrane under test under simulated different operating conditions; Step S4: Define the antifouling index and calculate the antifouling index of the membrane to be tested based on the data measured in Step S3; Step S5: Based on the antifouling index obtained in Step S4, obtain the quantitative evaluation results of the membrane under test; The different operating conditions in step S3 include accelerated pollution condition and wind and solar fluctuation condition. Under the accelerated pollution condition, the accelerated testing device continuously adds simulated catalyst particles; under the wind and solar fluctuation condition, the accelerated testing device adds simulated catalyst particles in a pulsed manner.

2. The method according to claim 1, characterized in that, Step S2 includes testing the background resistance of the accelerated testing device in a membrane-free state. The sheet resistance of the membrane under test was obtained by testing without adding simulated catalyst particles. , where T is the electrolyte temperature; The initial surface resistance of the diaphragm under test The surface resistivity of the diaphragm to be tested Background resistance of the accelerated testing device The difference is expressed as: 。 3. The method according to claim 2, characterized in that, Step S3 includes running the accelerated testing device and monitoring the sheet resistance of the membrane under test in real time. Changes in electrolyte turbidity and particle concentration in the electrolyte; Under the accelerated pollution condition, the current density is 0.1-1.0 A / cm². 2 The current density remains constant within the specified range, under the wind and solar fluctuation conditions, between 0.1 and 1.0 A / cm². 2 Within the range of 0.2-0.8-0.2 A / cm 2 Fluctuations occur in a cyclical manner.

4. The method according to claim 3, characterized in that, The expression for the anti-pollution index in step S4 is: in, The time required for the surface resistance to rise to twice its initial value; This represents the concentration of the added particles; Represents current density; anti-pollution index The larger the value, the stronger the anti-fouling ability of the membrane under test.

5. The method according to claim 4, characterized in that, The pretreatment in step S1 involves soaking the cut diaphragm to be tested in a 30% KOH solution for 24 hours. The simulated catalyst particles are electrode detachment powder from the actual electrolytic cell after operation or are obtained by mixing Raney nickel powder and nickel oxide powder in a mass ratio of 1:5-5:1; the particle size of the Raney nickel powder and nickel oxide powder is 0.5-50 μm.

6. An accelerated testing device for the antifouling performance of an alkaline water electrolysis hydrogen production membrane used to implement the method of any one of claims 1-5, characterized in that, The device includes an electrolytic cell module, an electrolyte circulation module, a particle quantitative dosing module, and an online monitoring module.

7. The apparatus according to claim 6, characterized in that, The electrolytic cell module is an electrolytic cell used to realize the electrolysis of water and the deposition of particulate matter; The electrolyte circulation module includes a storage tank, a circulation pump, a flow meter, a temperature control unit, an electrolytic cell, and a turbidimeter; The particle quantitative dosing module includes a simulated catalyst particle quantitative dosing device installed on the electrolyte circulation loop formed by the electrolyte circulation module; The online monitoring module is an electrochemical workstation, which is connected to the electrodes in the electrolytic cell and is used to measure the surface resistance of the membrane in the electrolytic cell in real time.

8. The apparatus according to claim 7, characterized in that, The electrolytic cell has a zero-gap structure, with nickel braided mesh, nickel stretched mesh or nickel foam electrodes on both sides, and the diaphragm to be tested sandwiched in the middle. The electrolyte circulation loop starts from the storage tank, passes through the circulation pump, flow meter, temperature control unit, electrolytic cell and turbidity meter in sequence, and finally returns to the storage tank. The simulated catalyst particle quantitative dosing device is used to continuously or pulsedly add simulated catalyst particles to the storage tank.

9. The apparatus according to claim 8, characterized in that, The storage tank serves as the starting and ending point of the electrolyte circulation loop and is used to store the electrolyte; the circulation pump is used to provide circulation power to ensure the continuous flow of the electrolyte. The flow meter is used to measure the flow rate of electrolyte into the electrolytic cell module in real time; The temperature control unit is used to maintain the stability of the electrolytic cell module temperature, and the temperature control range of the temperature control unit is 60-90℃; the turbidimeter is used to monitor the turbidity of the electrolyte in real time and characterize the concentration of suspended particles therein; several pressure sensors are installed on the electrolyte circulation loop, and the pressure sensors are connected to the electrolytic cell pressure tap through pressure guide pipes to monitor the pressure in the electrolyte circulation loop in real time.